KEGIATAN RAMADHAN BERSAMA SISWA DI SMP NEGERI 3 TANJUNG PURA UNTUK MEMANTAPKAN PEMAHAMAN AGAMA ISLAM - Anggara, Ari; Ramadhan, Syahru; Mahardika, Rafi; Ridha, Zaifatur (El-Madaniyah : Jurnal Pengabdian Masyarakat, 2024)
This community service is carried out in order to fill activities in the month of Ramadan. The activity carried out was in the form of an express Islamic boarding school at SMP Negeri 3 Tanjung Pura. This express Islamic boarding school was implemented with the aim of strengthening understanding of Islam for class IX students at SMP Negeri 3 Tanjung Pura. This express Islamic boarding school activity was carried out by the PKM team, namely STAI Jam'iyah Mahmudiyah lecturers as supervisors and students as presenters and event organizers. In implementation, activities are carried out for a day using lecture and demonstration methods related to Islamic religious material. Apart from that, students were also invited to play games with prizes which of course the students were very enthusiastic about. The results of the evaluation of Islamic boarding school activities based on student interviews show that students are very enthusiastic about participating in Ramadhan activities and students gain knowledge and insight into understanding Islam.